Eating with others and meal location are differentially associated with nutrient intake by sex: The Diabetes Study of Northern California (DISTANCE) - Pachucki, Mark C. (Appetite, 2018)
Though eating with others is often a social behavior, relationships between social contexts of eating and nutrient intake have been underexplored. This study evaluates how social aspects of eating – frequencies of eating meals with others, meals prepared at home, and meals outside the home – are associated with nutrient intake. Because diet improvement can reduce complications of diabetes mellitus, we surveyed a multi-ethnic cohort of persons with type 2 diabetes (n=770) about social aspects of diet (based on 24h recalls). Sex-stratified multiple regression analyses adjusted for confounders assessed the relationship between frequency of eating with others and nutrient intake (total energy, energy from fat, energy from carbohydrates, Healthy Eating Index/HEI, Dietary Approaches to Stop Hypertension/DASH score). Although there was slight variation in men’s versus women’s propensity to share meals, after adjustment for confounders, there was no consistently significant association between meals with others and the 5 nutrient intake measures for either men or women. The directions of association between categories of eating with others and diet quality (HEI and DASH scores) – albeit not significant – were different for men (positive) and women (mostly negative), which warrants further investigation. The next analyses estimated nutrient intake associated with meals prepared at home, and meals consumed outside the home. Analyses indicated that greater meal frequency at home was associated with significantly better scores on diet quality indices for men (but not women), while meal frequency outside the home was associated with poorer diet quality and energy intake for women (but not men). Better measurement of social dimensions of eating may inform ways to improve nutrition, especially for persons with diabetes for whom diet improvement can result in better disease outcomes.